Circadian clock dysfunction in human omental fat links obesity to metabolic inflammation - Eleonore Maury (Nature Portfolio, 2021)
Whether chronic inflammation contributes to metabolic disease through the dysregulation of circadian systems remains incompletely understood in humans. Here the authors show that circadian clock function is perturbed in adipose tissue from individuals with obesity, and that inhibition of NFkB improves clock function.